From the Field to Dining Table: Pesticides Residues - GC, Y.D.; Palikhe, B.R. (Journal of Agriculture and Environment, 2021)
This review article aims to present an overview of pesticide residue, focusing from the field to dining table and on the impact on health. This study also shows that an information campaign regarding pesticide use and food safety for farmers and consumers. The methodology is based on previous research, relevant studies, published and unpublished sources and authors’ own experiences. The work is only a review-based study. Food is a more basic need of man than shelter and clothing. The public is concerned about the presence of pesticide residues in foods. Pesticide residues in foods, farmers’ exposure to pesticides, and environmental pollution are serious concerns in Nepal. Risks from pesticides are high because of the lack of knowledge of farmers, limited training and awareness on the safe production of food crops, the absence of an effective code of practices, alternatives to chemical pesticide and inadequate residue monitoring Increasing awareness regarding good nutrition through quality food is creating a rise in the demand for vegetables and fruits and other crops. Despite great demand for safe vegetables, the supply of vegetables labeled as safe or organic is still limited. As growers are in a hurry to sell their produce, they do not wait or abide by the waiting period. As a result, the pesticide residues, left to variable extent in the food materials after harvesting, are beyond the control of consumer and have deleterious effect on human health. The consumer must think twice before eating veggies and biting into that fruits. Pesticides in the field do show up on our dinner plates or onto our kitchen tables. These pesticides often end up on dinner table. Consumers are not aware of food safety. The concentration of pesticide residues in the vegetable crops from the IPM field was considerably lower, suggesting a greater ability of IPM systems to reduce the dietary risks from exposure to pesticides. However, this is an alarming situation.